The EU's Energy Union: A Sustainable Path to Energy Security?. Issue 1 (2nd January 2016) - Siddi, Marco
Abstract: The Ukraine crisis and subsequent tensions in relations with Russia urged the European Union to diversify its energy suppliers and integrate the energy markets of member states. However, the EU does not seem to have a clear strategy to strengthen its energy security. Member states are reluctant to relinquish control over their energy policy. Moreover, the diversification of fossil fuel suppliers may lead to new dependencies on authoritarian states, while the emphasis on unconventional energy sources may delay the development of renewables. A coordinated focus on renewable energy, coupled with investments in energy efficiency, appears to be the most forward-looking and climate-friendly way of reducing external dependencies.